Оцінка еколого-генетичного різноманіття роду Vigna savi з використанням біотехнологічних методів – ISSR маркерів - Головань, Л. В.; Чуприна, Ю. Ю.; Близнюк, Ольга Миколаївна; Масалітіна, Наталія Юріївна; Бєлінська, Анна Павлівна; Бєлих, Ірина Анатоліївна (Національний технічний університет "Харківський політехнічний інститут", 2021)
The world's genetic resources of plants are the main source of improving crops for decades to come. The gene pool of plants has a hidden resource of new genes, or their combinations, including - selection-important features. The study of the potential of the plant gene pool with the main biological and economic characteristics allows to expand the genetic base of crops for the successful implementation of breeding programs in various areas. The genus Vigna has about 200 species that are grown in warm regions of the planet. The centers of origin of the species are in Africa, but mung beans, urd, azuki and rice beans are of Asian origin. The collection includes 20 specimens belonging to 7 species of the genus Vigna: V. aconitifolia (Jacq.) Marechal (willow aconitolista, mott) – 3 specimens, V. angularis (Willd.) Ohwi et Ohashi (adzuki) – 4, V. radiata (L.) R. Wilczek (mash) – 4, V. umbellata (Thunb.) Ohwi et Ohashi (vigna rice) – 4, V. unguiculata (L.) Walp. (Chinese) – 5. These are mainly local varieties, about 10 % are breeding varieties and 1% are forms that grow in nature. The multifaceted use of cultivated species of the genus Vigna contributed to their spread throughout the tropical, subtropical and temperate zones of the globe. They are economically important crops in many developing countries. Geographical analysis showed that most of the samples came from the areas of world agriculture and crop formation. most samples of V. radiata, V. mungo, V. aconitifolia, V. trilobata, V. umbellata were obtained from India and Pakistan, V. angularis – from East Asia and China, V. unguiculata – East Africa (Ethiopia, Kenya), V unguiculata – from China. However, the exact place of domestication of this culture has not been established, and in numerous sources of literature can be found different opinions of scientists on the origin of cowpea and the centers of its diversity. Recently, using the methods of molecular genetics (RAPD, AFLP and others) it was confirmed that the northern part of Africa is the center of origin of the cultured, because the wild types of West Africa are closer to cultural forms than the wild types of East and South Africa. It should be noted that the species of cowpea have a significant intraspecific polymorphism. The samples showed strong variability of morphological and economically valuable features. Such a wide range of variable variability is due to the places of cultivation of samples, different environmental conditions (plains, mountains, climate). According to the results of the evaluation of the DNA polymorphism of cowpea using molecular genetic markers, it was found that the species of cowpea involved in the study are characterized by a high level of DNA polymorphism, which averaged 78.6 %. 145 loci were identified, including 31 unique, specific to a particular sample, and 31 monomorphic, characteristic of all samples. Monomorphic loci are conserved regions of DNA that indicate the common origin of the species of cowpea involved in the work, and can be used as genus and species-specific markers. Unique loci indicate genetic divergence of the studied material and can serve as markers of certain samples. The average level of intrapopulation polymorphism of cowpea DNA (37.2–93.8 %, depending on the genotype) was established, which indicates the existence of significant variability in the studied samples of cowpea. It shows a high level of genetic divergence of cowpea species and testifies in favor of the polyphyletic theory of their origin.

Світові генетичні ресурси рослин є основним джерелом покращення сільськогосподарських культур на найближчі десятиліття. Генофонд рослин має прихований ресурс нових генів, або їх поєднань, у тому числі – селекційно-важливих ознак. Вивчення потенціалу рослинного генофонду з основним біологічним та господарським ознакам дозволяє розширити генетичну базу культур для успішної реалізації селекційних програм різного напряму. Рід Вигна (Vigna) нараховує близько 200 видів, які вирощуються в теплих регіонах планети. Центри походження видів знаходяться в Африці, але маш, урд, адзукі та рисова квасоля мають азіатське походження. Колекція нараховує 20 зразків, які належать до 7 видів роду Vigna: V. aconitifolia (Jacq.) Marechal (вигна аконитолиста, мотт) – 3 зразки, V. angularis (Willd.) Ohwi et Ohashi (адзукі) – 4, V. radiata (L.) R. Wilczek (маш) – 4, V. umbellata (Thunb.) Ohwi et Ohashi (вигна рисова) – 4, V. unguiculata (L.) Walp. (китайська) – 5. В основном, це – місцеві сорти, біля 10 % – селекційні сорти та 1% складають форми, які ростуть в природі. Багатогранне використання культивованих видів роду Vigna сприяло їх поширенню по всій території тропічних, субтропічних та помірних зон земної кулі. Вони є економічно важливими культурами у багатьох країнах, що розвиваються. Аналіз географічного показав, що більшість зразків надійшли від ареалів світового землеробства та формотворення культур. Більшість зразків V. radiata, V. mungo, V. aconitifolia, V. trilobata, V. umbellatа отримано з Індії та Пакистану, V. angularis – зі Східної Азії та Китаю, V. unguiculata – східної Африки (Ефіопія, Кенія), V. unguiculata – з Китаю. Однак конкретне місце одомашнення цієї культури точно не було встановлено, і в численних джерелах літератури можна зустріти різні думки вчених з питань походження вигни та центрів її різноманітності. Останнім часом, використовуючи методи молекулярної генетики (RAPD, AFLP та інших) було підтверджено, що північна частина Африки є центром походження окультуреної, оскільки, дикі типи Західної Африки більш близькі до культурних форм, ніж дикі типи Східної та Південної Африки. Варто відмітити, що види вигни мають значний внутрішньовидовий поліморфізм. У зразків відмічена сильна мінливість морфологічних та господарсько-цінних ознак. Такий широкий розмах варіативної мінливості обумовлений місцями культивування зразків, різними екологічними умовами (рівнини, гори, клімат). За результатами оцінки поліморфізму ДНК вигни з використанням молекулярно-генетичних маркерів встановлено, що залучені в дослідження види вигни характеризуються високим рівнем поліморфізму ДНК, який в середньому становив 78,6 %. Ідентифіковано 145 локусів, серед яких 31 унікальний, притаманних певному зразку, і 31 мономорфний, характерних для всіх зразків. Мономорфні локуси є консервативними ділянками ДНК, які свідчать про спільне походження залучених в роботу видів вигни, і можуть бути використані як родо- і видоспецифічні маркери. Унікальні локуси свідчать про генетичну дивергенцію досліджуваного матеріалу і можуть слугувати маркерами певних зразків. Встановлено середній рівень внутнішньопопуляційного поліморфізму ДНК вигни (37,2–93,8 %, залежно від генотипу), що свідчить про існування значної мінливості у досліджуваних зразків вигни. Він показує високий рівень генетичної дивергенції видів вигни і свідчить на користь поліфілетичної теорії їх походження.
Assessment of ecological and genetic diversity of the genus Vigna savi using biotechnological methods - ISSR markers
Keywords: вигна; генофонд; амплікони; поліморфізм; маркери; ДНК; локус; походження; еволюція; ISSR; pasture; gene pool; amplicons; polymorphism; markers; DNA; locus; origin; evolution